1999
DOI: 10.1046/j.1365-2133.1999.02622.x
|View full text |Cite
|
Sign up to set email alerts
|

Livedoid vasculitis: a manifestation of the antiphospholipid syndrome?

Abstract: Livedoid vasculitis, otherwise known as segmental hyalinizing vasculitis or livedo reticularis with summer ulceration, is a chronic disease with lesions affecting the feet and lower legs. Early lesions show petechiae, but characteristic features are recurrent, bizarrely shaped ulcers that heal to leave hyperpigmentation and atrophie blanche. The aetiology of the disorder is unknown, but the histology shows fibrin deposition within both the wall and lumen of affected vessels. The absence of a sufficient perivas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 26 publications
4
68
1
13
Order By: Relevance
“…40 Cutaneous ulceration and necrosis have been described in association with circulating LA, 41 and LA and ACAs have been reported in patients with livedoid vasculopathy. 4,42,43 The prevalence of LA in our study group is higher than that in the healthy population (8%). 44 Similarly, 28.6% of our patients were found to have ACA, compared with 5% to 12% reported in healthy persons, although 1 study reported a 51.6% prevalence of IgG ACA in healthy elderly subjects.…”
Section: Commentmentioning
confidence: 61%
“…40 Cutaneous ulceration and necrosis have been described in association with circulating LA, 41 and LA and ACAs have been reported in patients with livedoid vasculopathy. 4,42,43 The prevalence of LA in our study group is higher than that in the healthy population (8%). 44 Similarly, 28.6% of our patients were found to have ACA, compared with 5% to 12% reported in healthy persons, although 1 study reported a 51.6% prevalence of IgG ACA in healthy elderly subjects.…”
Section: Commentmentioning
confidence: 61%
“…Although atrophie blanche is a consequence of the lesions of livedoid vasculopathy, it is not pathognomonic of this disorder and can occur in association with other conditions such as stasis dermatitis and collagen vascular diseases. 2,4,6,7 Although it is quite distinctive from a vasculitis or immune-mediated process, livedoid vasculopathy has been confused with small vessel vasculitis in the past and can be misdiagnosed, as demonstrated by our patient's diagnostic history. The term segmental hyalinizing vasculitis was commonly used to describe livedoid vasculopathy in the 1970s.…”
Section: Commentmentioning
confidence: 94%
“…The aetiology of the disorder is unknown. Skin biopsy argues against a real vasculitis and shows fibrin deposition within affected walls of vessels and thrombus formation within the lumen [1]. Livedoid vasculopathy seems to be thrombo-occlusive vasculopathy.…”
Section: ■ Livedoid Vasculopathymentioning
confidence: 98%
“…It can be associated with systemic disorders like SLE or present in an "ideopathic" form [60]. A number of studies report about different coagulation abnormalities: elevated fibrinopeptid A [62], defective release of vascular plasminogen activator [73], decreased thrombomodulin expression [100] and protein C deficiency [4].Acland et al have suggested that livedoid vasculopathy may be a manifestation of antiphospholipid syndrome [1].…”
Section: ■ Livedoid Vasculopathymentioning
confidence: 99%